The concussion recovery questionnaire (CORE-Q): conceptual model development and item generation of a concussion-specific measure of functional status. (15th April 2020) - Van Ierssel, Jacquie; Sveistrup, Heidi; Marshall, Shawn; Graham, Ian
ABSTRACT: Introduction : Defining and measuring limitations in functional status post-concussion has been challenging, as generic measures do not accurately reflect issues most relevant to adults with persistent post-concussion symptoms. Purpose : To develop a new concussion-specific measure of functional status for use in clinical practice and intervention trials. Method : We developed a conceptual model of functioning based on concepts identified from a previous qualitative study with persons with concussion and clinicians. An initial set of questionnaire items was generated from the concepts, codes, and conceptual model. Items were refined using cognitive interviews elicit feedback on their relevance and acceptability. Results : We developed an initial set of 145 items categorized by concepts that were reduced to 50. Our final item set resulted in the CO ncussion RE covery Questionnaire, which contains a total of 53 items split into 3 separate scales: the Post-Concussion Functional Scale, Concussion Modifiers Scale, and Global Functional Recovery Scale. Conclusion : The new Concussion Recovery Questionnaire is a self-reported measure of functional status for monitoring outcomes in clinical practice and in clinical intervention trials following concussion. Further studies are necessary to provide evidence of the measure's psychometric properties and to determine the questionnaire's ability to facilitate clinical decision-making.